Data Analysis and Prediction of COVID-19 Using Machine Learning Models - Dr. E. Laxmilydia,Dr.Pavan Kumar,Vydarsi Sitarama Prasad,Chinmaya (International Journal of Advanced Science and Technology, 2020)
Breakout of novel corona virus from China got spread to various countries all over the world. The symptoms of the affected patients were hard to be sorted through self defection. The rapid increase of the virus cases spread through air, physical touch, and direct interaction from one person to another and to things. COVID-19 begins with respiratory illness which also includes fever, sore throat, cough and water from eyes. Increase of patients at various places, this paper identifies prediction model to predict and analyze COVID-19 virus using machine learning Time series forecasting prediction models such as Holt’s Linear Model, Holt’s winter Model, Prophets Predictions. By comparing the worst affected countries those reside beside India using machine learning prediction models from kaggle Coronavirus COVID-19 repository dataset, we can predict the rapid changes in India.